The Algorithm of Information and the Origin of Basic Particles (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Everything is information because everything will inform you about itself through our senses, there is no other way to say it when discussing the philosophy of science. All information has similar basic characteristics including randomness. The reality of randomness gave the concepts to the theory of the algorithm of information the basis of all degrees of randomness. Everything is about relationships; the algorithm of information is the tool existence uses to determine the chances of relationships. If everything is about relationships, then relationships must begin with the particles. Not the basic particles having relationships with other basic particles as it was first postulated. The basic particle itself must be the result of an event and thus a relationship, it was not always there. This paper aims to shed some light on the question of where do particles come from? What relationships led to the event that created elementary particles?